Effective DNA extraction method for metagenomic analysis of rhizosphere bacteria from mangrove sediments - Siti Maysaroh; Meutia Samira Ismet; Beginer Subhan; Rita Andini; Enny Rimita Sembiring; Nurlita Putri Anggraini (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Mangrove, Rhizophora mucronata, grows in the intertidal area, which contains much organic matter and varying salinity. The organic matter content is influenced by the bacterial community that inhabits the ecosystem, but information regarding the bacterial community, especially in the mangrove root system, is not widely available. There are several challenges in completing this information, one of which is that the method used is still in a conventional form. Developments in environmental DNA analysis can support and complement this information. However, this method must be optimized because the organic matter content and salt variations affect the extraction results. Thus, this study aimed to determine the optimal approach for extracting bacterial DNA from mangrove sediments. The analysis used two methodologies: manual DNA extraction techniques based on buffer modification and DNA extraction kits. There were four different treatments, namely the soil DNA isolation plus kit (M1), the fecal / soil microbial quick-DNA miniprep kit (M2), glass powder with charcoal (M3), and glass powder with skimmed milk (M4). DNA samples were obtained from each method and assessed for concentration and purity using a nanodrop. In addition, the resulting DNA's quality was analyzed using 1.5% agarose. The results obtained were in the M2 treatment, which showed optimal results compared to the others. M2 uses a bead-based beating and spin column method to achieve optimal DNA concentration through high molecular weight. The DNA obtained was also protein-free, and several samples were contaminated with humic acid, namely KL.S1, KL.S4, and T7.S4.Keywords:Bacteria 16SBead beatingDNA ExtractionSedimentSpin column